Exploring Sense of Humor in Steve Tv Show YouTube Channel - Sultan, Muliyani; Weda, Sukardi; Mahmud, Murni (Faculty of Languages and Literature, Universitas Negeri Makassar, 2024)
This study analyzes the videos on Steve's YouTube channel tv show with a focus on finding forms of humor and how the audience responds to delivered humor. The data is obtained from analyzing the conversation/interaction of the host, Steve Harvey, with the guest in the video. This study uses descriptive qualitative research methods to identify, sort, process information related to this study. The data is in the form of spoken words which are then analyzed based on the theory of Martin and Ford (2018). The results of this study show that the forms of humor from the videos in the Steve Tv show YouTube channel are spontaneous conversational humor forms, where we found 10 out of 11 types of this type of form. The types of humor found are irony, satire, sarcasm, overstatement, self-deprecation, teasing, replies to rhetorical questions, clever replies to a serious statement, double entendres, and puns. While the forms and types of humor that were not found were performance humor, jokes, accidental or unintentional humor, and transformation of frozen expression. For the results of our analysis related to the audience's response to delivered humor, it shows that they laughed, cheered, and clapped when the speaker made a statement that contained humor.